LIFECYCLE RITUALS OF THE M’NONG ETHNIC GROUP IN DAMRONG DISTRICT, LAMDONG PROVINCE: TRADITIONS AND CHANGES - Võ Thị Thùy Dung (Tạp chí Khoa học Đại học Đà Lạt)
M'nong people, the native ethnic group in Central Highlands, has unique cultural characteristics. With the M’nong people in Damrong district, the lifecycle rituals play an important role in the individual and community’s life. Nowadays, the lifecycle rituals of the M'nong have been changed by the effects of economic, cultural and social factors, etc. By studying the changes of the M'nong traditional lifecycle rituals, this article mentions some major reasons as well as directions in order to preserve and improve the values of the M'nong traditional lifecycle rituals in Damrong district, Lamdong province.